2007
DOI: 10.1007/s10705-007-9154-y
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic carbon dynamics of improved fallow-maize rotation systems under conventional and no-tillage in Central Zimbabwe

Abstract: Fallowing increases soil organic carbon (SOC) during the fallowing phase. However, this benefit is lost quickly during the cropping phase. The objective of this study was to evaluate SOC dynamics of an improved fallow-maize rotation under no-tillage (NT) and conventional tillage (CT) from time of fallow termination, through the next two cropping seasons. The treatments studied were improved fallows of Acacia angustissima (A. angustissima) and Sesbania sesban (S. sesban), natural fallow and continuous maize. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 32 publications
3
22
3
Order By: Relevance
“…In improved fallows, even though biomass accumulation apparently depends on fallow age, species, and amount of rainfall during the first years of establishment (Kass et al 1993;Mafongoya and Dzowela 1999), management seems to be crucial for carbon sequestration. For instance, results of this study showed that only 40% of C supplied by trees in improved fallows comes from the enrichment as timber trees; the remaining 60% represented trees naturally grown through secondary succession as other authors reported recently (Nyamadzawo et al 2008). The role of species is of crucial importance (Albrecht and Kandji 2003); hence this issue will require more research.…”
Section: Discussionsupporting
confidence: 70%
“…In improved fallows, even though biomass accumulation apparently depends on fallow age, species, and amount of rainfall during the first years of establishment (Kass et al 1993;Mafongoya and Dzowela 1999), management seems to be crucial for carbon sequestration. For instance, results of this study showed that only 40% of C supplied by trees in improved fallows comes from the enrichment as timber trees; the remaining 60% represented trees naturally grown through secondary succession as other authors reported recently (Nyamadzawo et al 2008). The role of species is of crucial importance (Albrecht and Kandji 2003); hence this issue will require more research.…”
Section: Discussionsupporting
confidence: 70%
“…Chivenge et al (2007) point out that tillage plays a significant part in influencing nutrient storage and release from soil organic matter. However, some of these practices lead to the break down in soil organic carbon and destruction of the soil structure resulting in increased runoff and soil and water losses (Nyamadzawo et al, 2008;Thierfelder & Wall, 2009). Deterioration in the structure of the soil can have both short and long term effects on the soil organic matter which in turn will affect soil water content, retention and plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…Elwell and Stocking (1988) reported losses of up to 50% of applied fertilisers in Zimbabwe. High levels of soil and water loss have been attributed to inappropriate tillage practices which have resulted in reduction of soil organic carbon and destruction of soil structure (Mrabet, 2002;Nyamadzawo et al, 2008b;Thierfelder and Wall, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The integration of improved fallowing and conservation tillage can further improve the soil hydraulic properties (Alegre and Rao, 1996;Norwood, 1994), soil water-holding capacity (Nyamadzawo et al, 2008a) and improve organic carbon stocks in soils (Nyamadzawo et al, 2008b). Improved fallows can play an important role in mitigating climate change through carbon sequestration.…”
Section: Introductionmentioning
confidence: 99%